1992
DOI: 10.1161/01.str.23.6.855
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and metabolic changes in crossed cerebellar hypoperfusion.

Abstract: Background and Purpose:The pathophysiology of crossed cerebellar diaschisis remains to be elucidated. The mechanism responsible appears to be deafferentation through the corticopontocerebellar tract, which terminates in the cerebellar gray matter. However, few studies have demonstrated the hemodynamic and metabolic changes in the cerebellar gray matter and pons in crossed cerebellar diaschisis.Methods: Using positron emission tomography in 24 patients with unilateral supratentorial stroke, we evaluated regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 34 publications
1
46
1
Order By: Relevance
“…Scale maximum and minimum values are 70 and 0 mL·100 mL −1 min −1 for CBF, and 8 and 0 mL/100 mL for CBV, respectively. (Yamauchi et al, 1992;Ito et al, 2002). However, the degree of decrease in CBF during hypocapnia was greater than that in CBV (approximately 40% decrease in CBF and 10% decrease in CBV), indicating a decrease in vascular blood velocity during hypocapnia.…”
Section: Figmentioning
confidence: 88%
“…Scale maximum and minimum values are 70 and 0 mL·100 mL −1 min −1 for CBF, and 8 and 0 mL/100 mL for CBV, respectively. (Yamauchi et al, 1992;Ito et al, 2002). However, the degree of decrease in CBF during hypocapnia was greater than that in CBV (approximately 40% decrease in CBF and 10% decrease in CBV), indicating a decrease in vascular blood velocity during hypocapnia.…”
Section: Figmentioning
confidence: 88%
“…With 85%, the occurrence of significant CCD after stroke in our study is quite high, but still in line with the literature. For example, PET-based studies reported incidence of CCD in 67% (Yamauchi et al, 1992) and 89% of patients (Miura et al, 1994). Two previous studies dealt with MRI-based detection of CCD: Yamada et al (1999) found an incidence of 80%, whereas Lin et al (2009) reported CCD in only 16% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Complementing these observations from functional brain imaging on the relationship between oxygen consumption and blood flow during decreases are earlier quantitative metabolic studies of a phenomenon known as cerebellar diaschisis (53,54). In this condition, there is a reduction in blood flow and metabolism in the hemisphere of the cerebellum contralateral to an injury to the cerebral cortex, usually a stroke.…”
mentioning
confidence: 95%
“…In this condition, there is a reduction in blood flow and metabolism in the hemisphere of the cerebellum contralateral to an injury to the cerebral cortex, usually a stroke. Of particular interest is the fact that blood flow is reduced significantly more than oxygen consumption (53,54). The changes in the cerebellum are thought to reflect a reduction in neuronal activity within the cerebellum due to reduced input from the cerebral cortex.…”
mentioning
confidence: 99%